Stratigraphy and sedimentary environments of the Villa María and Peña Colorada formations (Paleogene), Westernmost Argentine Plateau. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Peña Colorada Formation records the early stage of Andean foreland sedimentation over ~1,000 km2 in the north westernmost Argentine plateau (21°51’ S - 66°12’ W). The aim of the present contribution is to provide a detailed stratigraphic characterization of these deposits and the description of their sedimentary environments. Detailed stratigraphic observations conducted to the division of the Peña Colorada Formation in two formal units, the Villa María and Peña Colorada formations. Subsequently, these two formations were divided into members according to sedimentary facies, textural tendencies, the alternating presence of quartz, carbonate and gypsum veins, and the distinctive cementation of deposits by iron carbonate, silica, and calcium carbonate. Data suggest that sedimentation would have taken place in alluvial plains near sourcing sediments that were being actively uplifted.